Mucous dilution activity of non soluble ethylacetate fraction syrup of hibiscus flowers (Hibiscus rosa-sinensis L.) at cow intestinein vitro - Mimiek Murrukmihadi; Subagus Wahyuono; Marchaban .; Sudibyo Martono (Indonesian Journal of Pharmacy, 2011)
Previous  study  indicated  that  ethylacetate  insoluble  fraction  of  ethanol extract  of  Hibiscus  flowers  (Hibiscus  rosa-sinensis L.)  were  able  to  dilute intestine cattle mucous in vitrothat was often associated with mucolytic activity.In  this  study,  syrup  preparation  of  various  concentrations  of  these  fractions (1.20,  1.60  and  2.00%)  was  tested  for  its  ability  to  dilute  of  mucous.  Each  of syrup  concentrations  was  mixed  with  20%  buffer  Phosphate  (pH,  7)  at  equalproportion (1:1 v/v), the resulting mixtures were tested for their ability to dilute mucous  in  vitro. Mucous  dilution  was  observed  by  flow  time  recorded in  the viscosimeter.  The  study  showed  that  all  syrup  concentrations  (1.20,  1.60, 2.00%) exhibited mucous dilution effect compared tonegative control and syrup concentration  at  2.00%  was  comparable  to  positive  control  acetylsistein  0.1% (p<0.05). Therefore, there was a possibility that thispreparation could be used as mucolytic.Keywords: Hibiscus rosa-sinensisL., viscosity, mucous dilution, mucolytic